2021
DOI: 10.1038/s41598-021-97185-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electrical grounding conditions on plasma–liquid interactions using Thomson scattering on a pulsed argon jet

Abstract: The interaction between an argon plasma jet excited using microsecond duration voltage pulses and a liquid target was examined using Thomson scattering to quantify the temporal evolution of the electron density and temperature. The electrical resistance between a liquid target and the electrical ground was varied from 1 to $$680\, \text {k}\Omega $$ 680 k Ω to mimic different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 36 publications
4
20
0
Order By: Relevance
“…The influence of the grounding conditions of a target under plasma exposure has been examined before regarding the electronic properties of the discharge. For a different coaxial-plasma jet operated using argon gas instead of helium and 5 s pulses (16 kHz), it was shown that the resistance of a conductive liquid target towards the ground determines whether it behaves as a DBD-type discharge (for a high impedance path to ground) or a DC-type (low impedance path to ground) 20 , 28 . This had significant consequences for the temporal dynamics of electron density and temperature in the center of the plasma plume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the grounding conditions of a target under plasma exposure has been examined before regarding the electronic properties of the discharge. For a different coaxial-plasma jet operated using argon gas instead of helium and 5 s pulses (16 kHz), it was shown that the resistance of a conductive liquid target towards the ground determines whether it behaves as a DBD-type discharge (for a high impedance path to ground) or a DC-type (low impedance path to ground) 20 , 28 . This had significant consequences for the temporal dynamics of electron density and temperature in the center of the plasma plume.…”
Section: Discussionmentioning
confidence: 99%
“…When the material is in direct contact with a plasma, the electric fields are induced by surface charge deposition and therefore this approach gives a way to examine the influence of the plasma on the target. This is complementary to other diagnostic techniques for the study of electrical properties of a plasma which focus on the characterization of the plasma plume, such as Thomson scattering, Stark broadening, Stark shift, or coherent anti-Stokes Raman scattering 11 , 16 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The calibration may be performed by Raman scattering on a known amount of the molecular gas [160] or by Rayleigh scattering on a known amount of neutral gas particles [188]. In practice, the Thomson scattering method requires the use of high-power lasers for a sufficient signal and triple grating spectrometers or Bragg grating for the removal of Rayleigh scattering from atoms and molecules and a stray light [137,159,189]. Besides the stray light, the nonintrusive influence of a laser on the observed plasma should be verified, so laser heating, optical pumping, detachment of the negative ions etc, should be excluded [161].…”
Section: Thomson Scatteringmentioning
confidence: 99%
“…The Thomson scattering technique is successfully applied for the diagnostics of a bulk plasma in contact with liquid in several configurations [137,189,191,192]. Thomson scattering measurements in near-liquid surface plasma are extremely challenging due to the elastic laser scattering on the surface and due to a Raman scattering on liquid water [193].…”
Section: Thomson Scatteringmentioning
confidence: 99%
“…Thus, to detect Raman and Thomson scattering signals, the light near the laser line (Rayleigh scattering/stray light) should be effectively removed to prevent saturation of the detector. Such laser line rejection can be performed with multiple techniques such as a triple grating spectrograph [4][5][6][7][8][9][10][11][12], a vapor cell [13][14][15], a glass/interference filter [16], a physical mask [17,18], and a volume Bragg grating (VBG) filter [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%